The carboxy terminus of pp60c-src is a regulatory domain and is involved in complex formation with the middle-T antigen of polyomavirus. - Cheng, S H (1988)
A large number of mutations were introduced into the carboxy-terminal domain of pp60c-src. The level of phosphorylation on Tyr-416 and Tyr-527, the transforming activity (as measured by focus formation on NIH 3T3 cells), kinase activity, and the ability of the mutant pp60c-src to associate with the middle-T antigen of polyomavirus were examined. The results indicate that Tyr-527 is a major carboxy-terminal element responsible for regulating pp60c-src in vivo. A good but not perfect correlation exists between lack of phosphorylation at Tyr-527 and increased phosphorylation at Tyr-416, between elevated phosphorylation on Tyr-416 and activated kinase activity, and between activated kinase activity and transforming activity. Phosphorylation of Tyr-527 was insensitive to the mutation of adjacent residues, indicating that the primary sequence only has a minor role in recognition by kinases or phosphatases which regulate it in vivo. Three mutants which have in common a modified Glu-524 residue were phosphorylated on Tyr-416 and Tyr-527 and were weakly transforming. This suggests that other mechanisms besides complete dephosphorylation of Tyr-527 can lead to increased phosphorylation of Tyr-416 and activation of the transforming activity of pp60c-src. Furthermore, the residues between Asp-518 and Pro-525 were required to form a stable complex with middle-T antigen. The proximity of these sequences to Tyr-527 suggests a model in which middle-T activates pp60c-src by binding directly to this region of the molecular and thereby preventing phosphorylation of Tyr-527. Alternatively, middle-T binding may mediate a conformational change in this region, which in turn induces an alteration in the level of phosphorylation at Tyr-527 and Tyr-416.